2024
DOI: 10.1172/jci172460
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac noradrenergic deficiency revealed by 18F-dopamine positron emission tomography identifies preclinical central Lewy body diseases

David S. Goldstein,
Courtney Holmes,
Patti Sullivan
et al.

Abstract: BACKGROUND. In Lewy body diseases (LBDs) Parkinson disease (PD), and dementia with Lewy bodies (DLB), by the time parkinsonism or cognitive dysfunction manifests clinically, substantial neurodegeneration has already occurred. Biomarkers are needed to identify central LBDs in a preclinical phase, when neurorescue strategies might forestall symptomatic disease. This phase may involve catecholamine deficiency in the autonomic nervous system. We analyzed data from the prospective, observational, long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
(99 reference statements)
1
7
0
Order By: Relevance
“…More broadly, the application of such a detailed and thorough longitudinal, prospective protocol as that used in Goldstein et al ( 7 ), with highly compelling results, will stimulate not only an extension of this study but also the further development of available biomarker detection tools ( 11 ). For example, 123 I-MIBG SPECT, skin and gut α-synuclein immunofluorescence, or seed amplification assays from cerebrospinal fluid or nasal secretions also have the potential to identify prodromal or early disease in at-risk individuals, accelerating the development and testing of new disease-modifying therapies for the central Lewy body diseases.…”
Section: Future Implicationsmentioning
confidence: 96%
See 4 more Smart Citations
“…More broadly, the application of such a detailed and thorough longitudinal, prospective protocol as that used in Goldstein et al ( 7 ), with highly compelling results, will stimulate not only an extension of this study but also the further development of available biomarker detection tools ( 11 ). For example, 123 I-MIBG SPECT, skin and gut α-synuclein immunofluorescence, or seed amplification assays from cerebrospinal fluid or nasal secretions also have the potential to identify prodromal or early disease in at-risk individuals, accelerating the development and testing of new disease-modifying therapies for the central Lewy body diseases.…”
Section: Future Implicationsmentioning
confidence: 96%
“…In this issue of the JCI, Goldstein et al ( 7 ) report the results of the prospective, longitudinal PDRisk study (ClinicalTrials.gov NCT00775853) investigating an NIH-developed positron emission tomography (PET) tracer, 18 F-dopamine, to assess dysfunction of the cardiac noradrenergic system as a prelude to the development of PD and DLB. Though relatively small, this study demonstrated a remarkably accurate predictive value of low cardiac uptake of 18 F-dopamine for central Lewy body disease.…”
Section: Cardiac Noradrenergic Dysfunction As An Early Markermentioning
confidence: 99%
See 3 more Smart Citations